The Pivotal Role of Viruses in the Pathogeny of Chronic Lymphocytic Leukemia: Monoclonal (Type 1) IgG K Cryoglobulinemia and Chronic Lymphocytic Leukemia Diagnosis in the Course of a Human Metapneumovirus Infection - Jérémy Barben; Alain Putot; Anca-Maria Mihai; Jérémie Vovelle; Patrick Manckoundia (Viruses, 2021)
Background: Type-1 cryoglobulinemia (CG) is a rare disease associated with B-cell lymphoproliferative disorder. Some viral infections, such as Epstein–Barr Virus infections, are known to cause malignant lymphoproliferation, like certain B-cell lymphomas. However, their role in the pathogenesis of chronic lymphocytic leukemia (CLL) is still debatable. Here, we report a unique case of Type-1 CG associated to a CLL transformation diagnosed in the course of a human metapneumovirus (hMPV) infection. Case presentation: A 91-year-old man was initially hospitalized for delirium. In a context of febrile rhinorrhea, the diagnosis of hMPV infection was made by molecular assay (RT-PCR) on nasopharyngeal swab. Owing to hyperlymphocytosis that developed during the course of the infection and unexplained peripheral neuropathy, a type-1 IgG Kappa CG secondary to a CLL was diagnosed. The patient was not treated for the CLL because of Binet A stage classification and his poor physical condition. Conclusions: We report the unique observation in the literature of CLL transformation and hMPV infection. We provide a mini review on the pivotal role of viruses in CLL pathophysiology.